Renewable energy modelling - Song, Zhiwei (2015)
This report focuses on the issue of utilizing energy storage on module-level photovoltaic (PV) system to handle the solar irradiance fluctuations. The objective is to identify the optimal storage size that can achieve a balance between cost of storage and smoothing effect, and to explore possible ways of improving smoothing result to further reduce the storage size. Solar irradiance pattern study, Time characteristics study and Energy pulse study were conducted to understand the features of irradiance fluctuations and obtain an estimate of possible size of storage. Energy storage simulation simulated the performance of different storage sizes on smoothing effect based on actual local data. Possible ways of improving the performance were investigated. Finally, several related issues and concerns were discussed.